Hawaiian National Bibliography, 1780-1900 Volume 2: 1831-1850 - Forbes, David W. (University of Hawaii Press, 2000)
The second volume of the Hawaiian National Bibliography records the transformation of Hawai'i from a feudal system of government to a constitutional monarchy whose autonomy was recognized by the United States and the great powers of Europe. Here are referenced the formation of laws, a constitution, a bill of rights, and government reports. Political entanglements with Great Britain and France, the Provisional Cession of Hawai'i to Great Britain, and the restoration of sovereignty in 1843 are documented. Publications resulting from the United States Exploring Expedition under Captain Charles Wilkes are included. Also listed and described are theater bills, broadsides, and other ephemera, which illuminate the everyday life of the period
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Jan 2018)